Pengembangan Usaha Mikro Kecil dan Menengah bagi Penyandang Disabilitas Wonogiri dalam Mendukung Ekonomi Inklusif Daerah - Dwi Maryani Rispatiningsih; Eko Siswoyo; Mugiyo Mugiyo; Ayuning Wulan (Insan Kreasi Media, 2026)
Low participation of persons with disabilities in regional economic activities. This is due to a combination of factors, such as limited access to capital, lack of marketing networks, and the persistence of social stigma that views persons with disabilities as a group receiving assistance rather than as productive economic actors. As a result, persons with disabilities have fewer opportunities to develop their potential and contribute to regional economic development. The methods used in Community Service are participatory and community empowerment methods, which emphasize the active involvement of persons with disabilities in every stage of the activity. The results of the activities show that the community-based empowerment and collaboration approach, as implemented by Joglo Ayu Tenan Makerspace Yogyakarta and the YAKKUM Yogyakarta Rehabilitation Centre, is relevant for adaptation in the development of UMKM for persons with disabilities in Wonogiri Regency. This approach not only improves the technical and managerial skills of participants but also strengthens the confidence, motivation, and social participation of persons with disabilities in economic activities. This community service activity not only resulted in increased capacity for individual disability UMKM actors, but also produced a sustainable output in the form of the DIFARAJA e-commerce platform, which is expected to continue to be developed as a model of good practice in inclusive regional economic empowerment.